PERBANDINGAN EFEKTIVITAS FISIOTERAPI DENGAN DAN TANPA MCKENZIE EXERCISE VIA VIDEO TERHADAP PENINGKATAN KEMAMPUAN AKTIVITAS FUNGSIONAL LUMBAL PADA PASIEN LOW BACK PAIN DI RS DR BRATANATA DAN RSUD RADEN MATTAHER JAMBI - Andini Putri Alifia (Jurnal Medika Hutama, 2026)
Low Back Pain (LBP) is a common musculoskeletal problem that reduces quality of life. Conventional physiotherapy is frequently used, but the addition of video-based McKenzie Exercise as an independent exercise is believed to accelerate pain centralization and patient compliance. This study aimed to determine the difference in the effectiveness of physiotherapy with and without video-based McKenzie Exercise in improving lumbar functional ability in LBP patients. This quantitative study used a quasi-experimental pre-post-test control group design. A total of 40 subjects were selected using purposive sampling and divided into experimental and control groups. Data were evaluated using the Oswestry Disability Index (ODI) questionnaire and analyzed using the Paired Samples T-Test and Independent Samples T-Test. The results showed that the majority of respondents were female (60%), aged 46-65 years (45%), and had a high school education (52.5%). There was a significant improvement in functional ability before and after the intervention in both groups (p<0.05). The experimental group showed a greater average decrease in ODI scores (from 21.75 to 16.95) compared to the control group. However, the post-intervention comparison between the groups yielded p=0.185. In conclusion, physiotherapy with and without video guidance are equally effective in improving lumbar functional ability. Descriptively, the results of the video group were better, although not statistically significant due to the limited sample size and confounding factors.